Historia del derecho indiano - Sánchez Bella, Ismael; Hera, Alberto de la.; Díaz Rementería, Carlos (Madrid : Editorial MAPFRE, 1992)
"Survey of the basic elements of Spanish law regarding indigenous peoples includes 12 essays on topics ranging from historiography, formation of the concept derecho indiano, government of indigenous institutions, and economic/commercial institutions. Essays have short bibliographies, but no footnotes"--Handbook of Latin American Studies, v. 58.
Keywords: DERECHO INDIANO -- LEYES, ESTATUTOS, ETC -- HISTORIA